2003
DOI: 10.1021/ma034266c
|View full text |Cite
|
Sign up to set email alerts
|

Physical Gelation of Gelatin Studied with Rheo-Optics

Abstract: A rheo-optical device outfitted with a Peltier temperature control for rapid temperature changes has been constructed that allows simultaneous measurement of the optical rotation of light and the controlled-stress rheology. Optical rotation provides a direct in situ assessment of the extent of triple helix reversion in a gelatin solution undergoing physical gelation in the rheometer. Thermal gelation of gelatin was monitored over a wide range of concentrations and temperatures. Assuming dynamic scaling theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
101
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 47 publications
12
101
2
3
Order By: Relevance
“…That observation notwithstanding, it is important to consider whether our rapid gelation tests could correspond to the fast gelling regime of Guo et al [4] who argue that large values of α (∼0.7) are only associated with the slow gelling regime and are physically meaningless. But we have clearly established herein the rheometrical conditions under which rapid gelation produces low values of α which are physically meaningless.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…That observation notwithstanding, it is important to consider whether our rapid gelation tests could correspond to the fast gelling regime of Guo et al [4] who argue that large values of α (∼0.7) are only associated with the slow gelling regime and are physically meaningless. But we have clearly established herein the rheometrical conditions under which rapid gelation produces low values of α which are physically meaningless.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have identified a need to reexamine reported rheological exponents measured on physical gels [4]. That is the purpose of the work reported herein in which we test the hypothesis that, in some instances, the recording of anomalous values of rheological exponents may be due solely to the application of rheometrically inappropriate procedures.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The nucleation and growth of these cross-links leads to the formation of a percolating thermoreversible gelatin gel network. This process is revealed by the growth with time t of the shear elastic modulus G. After a lapse time t 0 associated with percolation of the polymer network, G first exhibits a rapid increase due to further nucleation and growth of cross-links [8,9]. It then crosses over to a slow regime in which G grows logarithmically with time, without any measurable trend towards saturation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration dependence of the zero-shear specific viscosity [19] [20] yields a concentration at the onset of the entanglement regime c E = 1 wt.%, so that the three systems tested in this work are well entangled polymer solutions. Their viscoelastic properties were characterized by the measurement of both the steady flow viscosity η(γ) and the first normal stress-difference N 1 (γ) for shear ratesγ in the range 10 −1 -10 2 s −1 .…”
Section: A Polymer Solutions: Preparation and Rheological Characterimentioning
confidence: 99%